Menanamkan Karakter Gemar Membaca pada Anak Melalui Gerakan Literasi Sekolah (GLS) di SD Negeri 131 Kota Jambi - Astuti, Dwi Puji; Raudhoh, Raudhoh (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
Introduction. Based on the results of the TIMSS and PIRLS survey obtained that the literacy ability of Indonesian students is in a state of concern, so one of the efforts made by the Indonesian government through the Ministry of Education and Culture is by issating the School Literacy Movement (GLS). The School Literacy Movement is an effort made thoroughly to make the school as a learning organization whose citizens are literate throughout life through public involvement. The lack of awareness of students to read results in the urgency of literacy needing to be instilled from elementary school age. Research Method. This study used descriptive qualitative methods with the determination of the subject purposive sampling. Result and Discussion. The results showed that SD Negeri 131 Kota Jambi has a GLS strategy in instilling reading character that is done through three (3) stages, namely the habituation stage, development and learning stages. At the habituation stage to familiarize children to read without a bill, the development stage to form reading interests with non-academic bills and the learning stage with academic bills. The impact of GLS strategy in instilling the character of reading in students in State Elementary School 131 can be said that GLS activities begin to instill a favorite or penchant for reading seen from the feeling of pleasure to read, the need for students to read, the desire to always read, the act of finding reading and follow-up. Supporting factors in the implementation of GLS are the active role of all school residents, educator training, the role of parents of students in the form of book donation and involvement in literacy activities and support from outside parties, namely Tanoto foundation, mobile library and student participation in the Evergreen Reading House program. An inhibitory factor is the absence of a dedicated space for libraries as well as different students' reading interests. Efforts to overcome these obstacles are to make a corner of the library as a temporary replacement for the library and make reading angles in each class and the need for commitment of all parties in running literacy programs.